APPLYING THE SOFTWARE PACKAGE TABLE CURVE 2D FOR COMPUTATION OF PROCESSING AIR MEDIUM TEMPERATURE DURING FREEZING IN A FREEZER AND DEFROSRING OF LOGS - Tumbarkova, Natalia; Deliiski, Nencho (Innovation in Woodworking Industry and Engineering design, 2017)
A mathematical description of the change in the processing air medium temperature Tm during freezing in a freezer and subsequent defrosting of logs using a software package Table Curve 2D v.5.01 has been suggested. This package allows for the selection of equations, which provides the best similarity between the calculated with them values of Tm during the log’s freezing and defrosting processes and the respective experimentally established data for Tm. The values of the coefficients in the selected equations have been determined in the work for the cases of decreasing in Tm in the range from about 20 оС to about –30 оС during separately 30 h freezing and of the following increasing in Tm up to about 20 oC during the subsequent 30 h or 50 h defrosting of 6 pine logs with diameter of 240 mm and length of 480 mm.